Crystal structure of the zinc-, cobalt-, and iron-containing adenylate kinase from Desulfovibrio gigas: a novel metal-containing adenylate kinase from Gram-negative bacteria - Mukhopadhyay, A. (2013)
J Biol Inorg Chem (2011) 16:51–61 DOI 10.1007/s00775-010-0700-8